2013
DOI: 10.1017/s204017441300007x
|View full text |Cite
|
Sign up to set email alerts
|

Renal echo-3D and microalbuminuria in children of diabetic mothers: a preliminary study

Abstract: Maternal diabetes has assumed epidemic relevance in recent years and animal studies have provided some evidence that it may cause abnormalities in renal development and a reduction in nephron endowment in the offspring; however, human data are lacking. The renal cortex contains ∼95% of the glomeruli and its volume could be taken as a surrogate measure of glomerular number; based on this assumption, we measured renal cortex volume and in addition, microalbuminuria in a homogeneous sample of 42 children of diabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 20 publications
0
18
2
1
Order By: Relevance
“…The assessment of kidney growth is currently performed using 2D or estimating renal volume with 3D ultrasound scans [9,10,11]; however, to date, no biochemical marker has been evaluated in association with renal volume reduction and IUGR. Cystatin C (Cys-C) is a strongly basic secretory nonglycosylated protein produced at a constant rate in all nucleated cells [12].…”
Section: Introductionmentioning
confidence: 99%
“…The assessment of kidney growth is currently performed using 2D or estimating renal volume with 3D ultrasound scans [9,10,11]; however, to date, no biochemical marker has been evaluated in association with renal volume reduction and IUGR. Cystatin C (Cys-C) is a strongly basic secretory nonglycosylated protein produced at a constant rate in all nucleated cells [12].…”
Section: Introductionmentioning
confidence: 99%
“…Included studies (n = 9) were published between 1994 and 2014 and were conducted in 12 countries including the United States of America, [28][29][30] Netherlands, 31,32 Canada, 33 France, 34 Italy 35 and Brazil. 36 The most common measures of kidney structure were kidney volume and length, while kidney function measures were albuminuria, albumin/creatinine and GFR.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Four studies did not specify the exact numbers for each sex. 29,31,35,36 There was a wide range in the age of offspring at the time of assessment, from late gestation to approximately 40 years of age.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…While one study found normal foetal kidney volume in diabetic pregnancies (pregestational diabetes and GDM pregnancies grouped together), 38 another found increased foetal kidney volume in pregnancies of women with GDM. 40 Overall, evidence for the extent to which GDM affects developing human kidneys is not robust. 40 Overall, evidence for the extent to which GDM affects developing human kidneys is not robust.…”
Section: Introductionmentioning
confidence: 99%
“…39 A third preliminary study reported reduced renal cortical volume and increased albumin excretion in 3-year-old children whose mothers had GDM, taken to suggest a reduction in nephron endowment and glomerular impairment. 40 Overall, evidence for the extent to which GDM affects developing human kidneys is not robust. It is unclear what effect a period of hyperglycaemia has on foetal kidney development and growth, and subsequent renal physiology and function.…”
Section: Introductionmentioning
confidence: 99%